On Birkhoff Angles in Normed Spaces - Hendra Gunawan; Muhamad Jamaludin; Mas Daffa Pratamadirdja (Journal of the Indonesian Mathematical Society, 2021)
Associated to Birkhoff orthogonality, we study Birkhoff angles in a normed space and present some of their basic properties. We also discuss how to decide whether an angle is more acute or more obtuse than another. In addition, given two vectors $x$ and $y$ in a normed space, we study the formula for Birkhoff `cosine' of the angle from $x$ to $y$ from which we can, in principal, compute the angle. Some examples will be presented.